Effects of B2O3 and MgO on the microwave dielectric properties of MgTa2O6 ceramics. Issue 18 (15th December 2019) - Dang, Mingzhao; Lin, Huixing; Yao, Xiaogang; Ren, Haishen; Xie, Tianyi; Peng, Haiyi; Tan, Zhenyu
Abstract: MgTa2 O6 is a very promising microwave dielectric material, but the residual Ta2 O5 which produced during the reaction process of MgO and Ta2 O5 with stoichiometric ratio limits its further development. In this study, B2 O3 and MgO sintering additives were applied to reduce Ta2 O5 phase and enhance the microstructure and microwave dielectric properties. Results show that B2 O3 has an advantages over MgO in improving the material properties, the best microwave dielectric properties (εr = 27.8, Qf = 184000 GHz, τf = 53 ppm/ o C) were acquired at x(B2 O3 ) = 0.5 wt%. The mechanisms of both B2 O3 and MgO additives were analyzed in detail.